Development of Flexible Antimicrobial Packaging Materials Against Campylobacter Jejuni by Incorporation of Gallic Acid Into Zein-Based Films - Alkan, Derya; Aydemir, Levent Yurdaer; Ceylan, Çağatay; Arcan, İskender; Yavuzdurmaz, Hatice; Atabay, Halil İbrahim; Atabay, Halil İbrahim; Ceylan, Çağatay; Yemencioğlu, Ahmet (American Chemical Society, 2011)
In this study, antimicrobial films were developed against Campylobacter jejuni by incorporation of gallic acid (GA) into zein-based films. The zein and zein-wax composite films containing GA between 2.5 and 10 mg/cm 2 were effective on different C. jejuni strains in a concentration-dependent manner. Zein and zein-wax composite films showed different release profiles in distilled water but quite similar release profiles at solid agar medium. Depending on incorporated GA concentration, 60-80% of GA released from the films, while the remaining GA was bound or trapped by film matrix. The GA at 2.5 and 5 mg/cm 2 caused a considerable increase in elongation (57-280%) of all zein films and eliminated their classical flexibility problems. The zein-wax composite films were less flexible than zein films, but the films showed similar tensile strengths and Young's modulus. Scanning electron microscopy indicated different morphologies of zein and zein-wax composite films. This study clearly showed the good potential of zein and GA to develop flexible antimicrobial films against C. jejuni.
Keywords: Campylobacter jejuni; Zein; Antimicrobial; Edible films; Gallic acid; Composite films